Treatment of refractory mycetoma by radiotherapy: a case study and review. Issue Volume 5:Issues 3(2021) (31st August 2021) - Gupta, Anil; Sharma, Daya Nand; Gupta, Somesh; Sharma, Seema; Dev, Tanvi; Singh, Suvesh; Mücke, Ralph; Micke, Oliver
Abstract: Mycetoma is a localized chronic subcutaneous infection caused by fungi. It is clinically characterized by a triad of tumefaction, sinuses, and discharge containing typical grains. Eumycetoma, a subtype, is characterized by a low cure rate. Long‐term medication and surgical excision are required to treat the infection. Radiotherapy, a less used modality of treatment, may provide a good salvage option for refractory eumycetoma. Herein, we present a case and a review of the literature of refractory eumycetoma of the foot where radiotherapy was used as a salvage treatment. In the present case, a dose of 17.5 Gy in five fractions was delivered, and the response was assessed as per the Response Evaluation Criteria in Solid Tumors 1.1, discharging grains status, and Dermatology Life Quality Index. The literature on the use of radiotherapy for mycetoma was found to be scanty. In the present case with radiotherapy, there was a partial radiological response, resolution of discharging grains, and improvement in the Dermatology Life Quality Index score. However, the benefit was short‐lived, but re‐irradiation and low‐dose radiotherapy resulted in sustained benefits until 15 months of follow up. The antiproliferative and anti‐inflammatory actions of radiotherapy can be exploited in the treatment of rare, medically difficult to treat mycetoma. This case report may serve as a basis for further evaluation.